GAMBARAN PENGETAHUAN, SIKAP DAN KETERAMPILAN PERAWAT RUANGAN AKASIA TENTANG EARLY WARNING SCORE : Overview Of Acasia Room Nurses' Knowledge, Attitude And Skills Regarding Early Warning Score - Sameni, Sherly Yashinta; subandi, andi; Mulyani, Sri (Program Studi Keperawatan Universitas Jambi, 2023)
Background: Early warning score is a process of early detection of patients before the occurrence of emergency conditions. The Akasia Room in Dr. Bratanata Jambi adopts EWS from the Royal Collage of Physicians, 2017. Nurses who have good knowledge as well as a positive attitude can easily apply skills about EWS thus reducing the length of patient care. To overview of the knowledge, attitudes and skills of nurses about the Early Warning Score at Akasia room Dr. Bratanata Jambi hospital. Methods: This study uses a quantitative research design with descriptive research methods and total sampling techniques, namely the number of samples used is the total of the total number of existing populations. Of the 16 samples, almost all respondents had good knowledge and one respondent had sufficient knowledge because they answered incorrectly in the EWS parameter category. All respondents had a positive attitude and carried out observations according to the number of scoring patients with Early Warning Score skills. Conclusion: The nurses in the Acacia room have good knowledge and a positive attitude so that the skills about the Early Warning Score are carried out in the form of documentation and observation in accordance with the number of patient scoring scores.